The Relationship between the Insight Levels of Sustainable Development to the Attitude of Environmental Concern in FKIP Unsyiah - Abdullah Abdullah; Djufri Djufri; Irma Kharisma (Universitas Syiah Kuala, 2019)
Environmental problems are complex problems that must be addressed immediately, and humans are the only educated agents who can save the environment so that environmental benefits can be felt sustainably. This study aims to determine the relationship between the level of insight into sustainable development (sustainable development) to the attitude of environmental care FKIP academic community Unsyiah. This research uses a descriptive correlational approach. Data collection techniques using questionnaires, blind observation, interviews, and documentation. Data analysis using Spearman correlation with a confidence level of 95% and processed using the SPSS 18.0 application. The results of the analysis show a correlation coefficient of 0.345 which means there is a sufficient correlation between the level of insight into sustainable development with an attitude of environmental awareness. The significance value obtained from the Spearman correlation test is 0.345 ( 0.05), meaning that there is a significant relationship between the level of insight into sustainable development with an attitude of environmental awareness. The correlation coefficient has a positive value of 0.345, so insights are positively and significantly related to caring attitudes. The results of this study indicate that the level of insight into sustainable development is positively related to the attitude of environmental awareness in the FKIPUnsyiah academic community.